What a Waste! Exploring the Human Reality of Food Waste from the Store Manager's Perspective. (April 2016) - Gruber, Verena; Holweg, Christina; Teller, Christoph
Food waste is a major problem in industrialized nations, and thus a better understanding of this phenomenon and its inherent complexity is imperative. As gatekeeper to the food supply chain, the retail and wholesale sector is a crucial actor in the pursuit of minimizing food waste. The authors draw on the perspective of marketing as exchange to provide a holistic exploration of food waste in retail and wholesale stores while taking into account the interconnectedness of the entire food supply chain. Through 32 semistructured interviews with store managers, the authors shed light on the issues of food waste and its human reality. The findings reveal the questionable ethics of discarding food; the societal, regulatory, and systemic constraints leading to the occurrence of food waste in stores; and the resulting moral burden on store managers. Building on these factors, the authors outline public policy recommendations in the areas of education and law and provide managerial recommendations for the better management of food waste.